Developing Premarital Relationship and Suitability: Sharī‘ah Principles in the Light of the Qur’an 4:3 - Fatima, Saleha; Siddiqui, Muhammad Saad (Islamic Studies, 2021)
Marital affairs are one of the most elaborated provisions of sharī‘ah directives. Like other fields, Islamic marital ideologies are also affected by globalization and cultural influences. This article aims to explore sharī‘ah principles to tackle modernized customs of premarital engagements inspired by non-Islamic practices. Usually, khiṭbah (a proposal of marriage) is considered the earliest stage of the premarital phase. However, the Qur’ān 4:3 mentions a condition that persuades someone towards khiṭbah. Usually dominated by sight, ṭāba is a sensitive humanly state that stimulates liking and love for someone. A close analysis of Islamic traditions reveals three developmental stages of ṭāba having thin membranes between them, separated and studied for possible implications in the twenty-first century. Contemporary studies on premarital behaviours and modern trends of Muslim courtship further elevate the significance of this study.